Displacement of the Mandibular Condyles Immediately after Herbst Appliance Insertion - 3D Assessment - Paula Loureiro Cheib; Lucia Helena Soares Cevidanes; Antonio Carlos de Oliveira Ruellas; Lorenzo Franchi; Wagner Fernando Moyses Braga; Dauro Oliveira; Bernardo Quiroga Souki (Turkish Journal of Orthodontics, 2016)

(untitled)
Objective:To test the following two hypotheses regarding the consequences of Herbst appliance (HA) insertion: 1) a significant clockwise mandibular rotation will occur and 2) the displacement of the condyles will follow the same magnitude of the changes of overjet (OJ) and overbite (OB).Methods:Virtual 3D surface models of 25 patients were generated from cone-beam computed tomographs taken before treatment and immediately after HA insertion. Scans were registered on the cranial base and were analyzed using point-to-point measurements, color-coded maps, and semitransparent overlays. Statistical tests included correlation and simple regression analysis.Results:Pitch rotation, ranging from −2.2° to 2.2° (mean, 0.2°), was observed in clockwise and counterclockwise directions. Condylar sagittal displacement presented a positive correlation with OJ changes. Each millimeter of OJ correction resulted in an anterior condylar displacement of approximately 0.95 mm. Vertical condylar displacement correlated with OB changes and varied mostly between 2 mm and 4.5 mm.Conclusion:Immediately after HA insertion, no significant clockwise mandibular rotation was observed. The condyles were displaced anteriorly and inferiorly. Condylar anterior displacement and OJ correction presented a ratio close to 1:1. The vertical displacement of the condyles did not follow the same magnitude of OB changes.